What Can Life Satisfaction Data Tell Us About Discrimination Against Sexual Minorities? A Structural Equation Model for Australia and the United Kingdom - Nattavudh Powdthavee; Mark Wooden (Institute for the Study of Labor (IZA), 2014)
Very little is known about how the differential treatment of sexual minorities could influence subjective reports of overall well-being. This paper seeks to fill this gap. Data from two large surveys that provide nationally representative samples for two different countries – Australia (the HILDA Survey) and the UK (the UK Household Longitudinal Study) – are used to estimate a simultaneous equations model of life satisfaction. The model allows for self-reported sexual identity to influence a measure of life satisfaction both directly and indirectly through seven different channels: (i) income; (ii) employment; (iii) health (iv) partner relationships; (v) children; (vi) friendship networks; and (vii) education. Lesbian, gay and bisexual persons are found to be significantly less satisfied with their lives than otherwise comparable heterosexual persons. In both countries this is the result of a combination of direct and indirect effects.
Keywords: I31; J71; 330; sexual orientation; sexual minorities; discrimination; life satisfaction; HILDA Survey; UKHLS